Rapid and sensitive electrochemical detection of microRNAs by gold nanoparticle-catalyzed silver enhancement. Issue 24 (5th October 2020) - Wen, Qilin; Liang, Xiaolin; Pan, Hongcheng; Li, Jianping; Zhang, Yun; Zhu, Wenyuan; Long, Zhixiang
Abstract : Using the proposed method the microRNA assay was successfully carried out in less than 70 min and the detection limit was as low as 15 fM. Abstract : MicroRNAs (miRNAs) have played a vital role in the regulation of gene expression and have been considered as potential biomarker candidates for early cancer diagnosis. Rapid and sensitive detection of microRNAs is highly desired. Here, we present a new method to rapidly and sensitively determine microRNAs based on the technology of gold nanoparticle catalyzed silver staining enhancement. The new method involves the sandwich hybridization of a capture probe immobilized on a magnetic bead, a reporter probe assembled on gold nanoparticles and a miRNA target, catalytic silver precipitation by gold nanoparticles, magnetic collection of the enhanced sandwich complex, dissolution of the silver precipitation and stripping detection. Using the proposed method the microRNA-7a assay was successfully carried out in less than 70 min and the detection limit was as low as 15 fM. The proposed biosensor may hold great promise in biological monitoring of microRNAs.